THE IMPLEMENTATION OF SKETCH TO STRETCH IN TEACHING READING COMPREHENSION AT THE EIGHTH GRADE OF SMPN 32 BULUKUMBA - Evi Ariana; Eny Syatriana (English Language Teaching Methodology, 2021)
This research aimed to find out whether there is any significant difference achievement between the students taught through sketch to stretch and the students taught through without sketch to stretch at the eighth grade of SMPN 32 Bulukumba. The students’ reading comprehension was restricted to two indicators namely main idea and supporting details. The researcher used a quasi-experimental research with two groups: one group as an experimental group and another group as a control group. The sample were class VIII.2 as an experimental group which consisted of 14 students and class VIII.3 as a control group which consisted of 14 students. The instrument of this research was reading test. The result of the research showed that the value of t-test in post-test both of groups was 2.519. it was higher than t-table namely 2.056 at the level of significant (p) = 0.05 with degree of freedom (df) = 26. The differences between t-test and t-table value was significant differences. It means that the Null Hypothesis (H0) was rejected an alternative (H1) was accepted. Therefore, it can be concluded that there is the significant differences achievement between the students taught through sketch to stretch and the students taught through without sketch to stretch.